Coronary atherosclerosis and periodontitis have similarities in their clinical presentation - Barbosa De Accioly Mattos, Marcelo; Bernardo Peixoto, Camila; Geraldo de Castro Amino, José; Cortes, Leandro; Tura, Bernardo; Nunn, Martha; Giambiagi-deMarval, Marcia; Sansone, Carmelo (Frontiers in Oral Health, 2024)
Background - periodontitis (PE) and coronary heart disease (CHD) possess multiple mechanisms for a putative association. This case-control study compared the periodontal status among CHD subjects to controls without CHD, while also investigating atheroma invasion by known periodontal pathogens. Methods - 161 subjects participated in this study were divided into three CHD groups: No CHD, chronic CHD, acute CHD. Additional analysis involved grouping subjects according to number of atheromas: no atheroma, 1-4 atheromas, 5-18 atheromas. Data were collected from medical records, periodontal examinations, and questionnaires that included demographic, behavioral, and oral health variables. Angiographic catheterizations were analyzed according to the number of atheroma lesions, lesion size, lesion location, and atheroma lesion stability. Lipoprotein profile, inflammatory markers and cells were analyzed. The microbiological branch added 30 individuals who had their atheroma lesion and subgingival plaque analyzed using polymerase chain reaction probes against the 16s region, red complex and Aggregatibacter actinomycetemcomitans’ DNA. Results - Subjects with CHD had high levels of systemic inflammatory markers and low levels of high-density lipoproteins compared to subjects without CHD. Subjects without CHD and clear coronaries had a prevalence of mild CAL, while individuals with more atheroma lesions had advanced CAL and more active PE. Subjects with more advanced CAL were 4 times more likely to have CHD compared to subjects with less, which is comparable to smoking. Only 4 subjects had the screened pathogens detected in atheroma, although these subjects also have the screened pathogens in subgingival plaque. However, 80% of atheromas had bacteria. Conclusions - CHD and PE showed similarities in progression while active PE led to more atheroma lesions that also tended to be larger in size.